Low Machining Parameters Produce High Cutting Performance when Machining AISI 1045 at Dry Cutting Conditions Using a CNC Lathe Machine - Rashidi, Iqmal Farhan; Tamin, Norfauzi; Rani, Ridhwan; Azlan, Umar Al Amani; Wahab, Norfariza Ab; Ismail, Anwar; Darmawan, Agung Setyo (Directorate for Research and Community Services, Institut Teknologi Bandung, 2025)
AISI 1045 medium-carbon steel is widely used for machining because of its excellent machinability. It balances strength and workability in various manufacturing applications, including machinery parts, gears, mold pins, automotive parts, crankshafts, bolts, and studs. The most significant disadvantage of AISI 1045 machining is that if the cutting parameters are not managed appropriately, it can affect the efficiency of the machining process, which involves tool life and product surface finish at dry cutting conditions. This study aims to determine suitable cutting parameters for AISI 1045, identify the optimum minimum tool wear (VB), and assess surface roughness (Ra). This study used various machining parameters at a cutting speed (Vc) of 35–53 m/min, feed rate (fr) of 0.15, and 0.5 mm/rev at a 1 mm constant depth of cut (DOC). The results showed that a Vc of 35 m/min and a fr of 0.15 mm/rev obtained the lowest average VB of 0.07 mm and Ra of 3.8 µm. This study found that low machining parameters produce high dry-cutting performance. This study provides guidelines for machinists to use appropriate cutting parameters when machining AISI 1045 under dry-cutting conditions at short machining times. In addition, it promotes sustainable machining and prevents air pollution from using coolants (chemical reactions).